TEMPERATURE ALARM ON IRON-BASED BLYNK PLAYSTORE APPLICATION - Sembodo, Budi Prijo; Mahardhika, Bagus Prima (Program Studi Teknik Elektro Universitas PGRI Adi Buana Surabaya, 2020)
In this era, practical, effectiveness and safety in activities are the necessities and demands of life where almost all people make it a priority in their lives. Effectiveness in activities will be obtained by the availability of technology that supports it all. Various efforts have been made by humans to make neat clothes so as to create a clean impression and support various activities, an example of the results of human efforts that are widely used to overcome this is by using an iron. In addition, the majority of the equipment still requires manual operation. Apart from the practical side, but does not eliminate the safety side. So here the author is interested in conducting research on the practicality of use which is later expected to make the use of irons more efficient, practical and safe. The measured parameter is how the DS18B20 temperature sensor functions as a temperature response receiver that sends a signal to the temperature sensor module which will activate or deactivate the iron through a smartphone. The results of this study that the device is able to send a signal to the smartphone and if the temperature produced by the iron exceeds the maximum limit a warning sign will appear on the smartphone, and the user can operate the iron online and remotely using a smartphone. The speed of response received by the tool is also to be forwarded to the iron or smartphone is also in accordance with needs.